JAWARA VALUES AS THE BASIC OF STRUCTURED PEER CONSULTATION MODEL - Deasy Khairun (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2023)
Jawara is someone who has a position and is part of the identity of the Banten people because of his physical strength, high-level knowledge, and highly educated. This study aims to reveal Jawara's values as the basis for the Structured Peer Consultation Model. The research method used is a quantitative survey method of 121 Jawara Banten in three regencies in Banten Province, namely Serang Regency, Lebak Regency, and Pandeglang Regency.  Data analysis was performed by testing the RASCH model. The general results of the research show that the values of the 121 respondents are in the high category. The research results have an important role, namely as a basis for the development of a structured peer consultation  model.